John Paul II on the Role of Culture in the Life of a Man and Nations (Economic and Political Thought, 2010)
The present article is an attempt to present John Paul II’s opinions onthe role of culture in the life of a man and nations, especially the Polishnation, which – deprived of its sovereign state – survived 123 years of nationalbondage retaining its language and identity. The author tries to show thePope’s stand on culture in a broad sense and its position in the history ofEurope and the processes of its economic, political and social integration.In the article the author proposes many interesting theses and hypotheseson John Paul II’s opinions on culture and his stand on culture creationprocesses as well as the influence of Christianity, especially the CatholicChurch, on the Polish culture and European culture. Echoing John Paul II,she proves that culture is one of the most important elements of national tiesthat are essential for the existence of nations.